Aktivitas Fungisida Ekstrak Daun Sirih (Piper Betle L.) Kultivar Beleng terhadap Jamur Fusarium Oxysporum f.sp. Vanillae Penyebab Penyakit Busuk Batang pada Vanili: Fungicidal Activity of Betel Leaves (Piper Betle L.) of Beleng Cultivar on Fusarium Oxysporum f.sp. Vanillae Causes Stem Rot in Vanilla - I Made Subrata; I Gusti Ayu Rai (Emasains : Jurnal Edukasi Matematika dan Sains, 2019)
This research was done in order to know inhibitory activity of beatle leaf the cultivar of Beleng extract and its mechanism against the growth of F. oxysporum f. sp. vanillae, that causal agent of steam disease on vanilla. Many effort have been done to control the disease such as the use of synthetic fungicide. In order to find other alternatives for controlling the disease, Beleng leaf were studied for their bioactivity against F. oxysporum f. sp. vanillae. The result of the study indicated that the crude extract of Beleng leaf at concentration 0.05%; 0.1%; 0.15%; 0.2%; 0.25%; 0.3% and 0.35% was able to inhibit the radial growth of F. oxysporum f.sp. vanillae on Potato Dextrose Agar (PDA) medium. The variation of crude extract concentration was found to influence the fungal growth on vanilla stem cutings on PD Broth medium. In addition, the crude extract of Beleng leaf was able to inhibit the spore germination and spore formation of F. oxysporum f. sp. vanillae on PD Broth medium. The fractination of Beleng leaf crude extract with Column Chromatography and Thin Layer Chromatography produced 15 fractions of compound, the fraction number VI which is made of three compounds with Rf value : 0.35; 0.55 and 0.78 efectively inhibited the growth of F. oxysporum f. sp. vanillae on PDA medium.